Antinomies of Anglo-American and Domestic jurisprudence in understanding the children’s rights issues - M. Yu. Burdin; I. L. Nevzorov; T. S. Tomliak (Law and Safety)
The article analyses the views of Anglo-American jurisprudence on the issues of children's rights in the context of similar national scientific works.